Empowering Women through BISP : The Effect of Women's Decision-Making Power on Reproductive Health Services Uptake in Pakistan - World Bank (Washington, DC, 2017)
This note examines the influence of household decision making on women's uptake of reproductive health services, using data from the Pakistan Social and Living Standards Measurement Survey (PSLM). In households where women have greater decision?making power, the note finds a significant and positive association with greater use of reproductive health services. In households where the influential decision maker is a male, the opposite effect prevails. These findings suggest that empowering women and increasing their ability to make decisions may increase their use of reproductive health services. The findings also suggest that policies directed toward improving women's use of maternity services must target influential male household members, whose understanding of the importance of maternity services is crucial to increase the effectiveness of health interventions. Improving financial and physical access to maternal health services is also critical to increasing their use and achieving the Millennium Development Goals (MDGs) related to maternal health. This paper contributes to the literature by applying several constructed indices composed of eight women's decision?making indicators to assess the relationship between women's decision making and their reproductive health services uptake. This paper also considers the influence of male household members (household heads or husbands) on decision making and women's uptake of reproductive health services.